2007
DOI: 10.1111/j.1469-8986.2007.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

It's worse than you thought: The feedback negativity and violations of reward prediction in gambling tasks

Abstract: The reinforcement learning theory suggests that the feedback negativity should be larger when feedback is unexpected. Two recent studies found, however, that the feedback negativity was unaffected by outcome probability. To further examine this issue, participants in the present studies made reward predictions on each trial of a gambling task where objective reward probability was indicated by a cue. In Study 1, participants made reward predictions following the cue, but prior to their gambling choice; in Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

75
472
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 476 publications
(551 citation statements)
references
References 32 publications
75
472
4
Order By: Relevance
“…Because in the original Gehring and Willoughby study events were included in which a small loss was the most advantageous outcome of a trial (because the other response option would have resulted in a greater loss), it appears that the FRN responds to the gain/loss status of an event as opposed to whether or not the choice was erroneous or disadvantageous. In other studies, a strong influence of context on the FRN elicited by losses and negative events has been reported [16]. …”
Section: Introductionmentioning
confidence: 81%
“…Because in the original Gehring and Willoughby study events were included in which a small loss was the most advantageous outcome of a trial (because the other response option would have resulted in a greater loss), it appears that the FRN responds to the gain/loss status of an event as opposed to whether or not the choice was erroneous or disadvantageous. In other studies, a strong influence of context on the FRN elicited by losses and negative events has been reported [16]. …”
Section: Introductionmentioning
confidence: 81%
“…While the negative deflection to unfavourable outcomes described above has been reported in a wide variety of circumstances, including simulated gambling (Hewig et al, 2007), guessing tasks Hajcak et al, 2005Hajcak et al, , 2007, time estimation tasks (Holroyd and Krigolsen, 2007;Miltner et al, 1997;Nieuwenhuis et al, 2005), and learning tasks (De Pascalis et al, 2010), the true nature of the FRN remains somewhat unclear, as this component is commonly superimposed on large amplitude P300 responses that occur immediately after it. It has been proposed that the reduced amplitude FRN observed following win outcomes may not be an actual attenuated response to these events, but is rather driven by larger P300 amplitudes following favourable outcomes (Yeung and Sanfey, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…It has been proposed that the reduced amplitude FRN observed following win outcomes may not be an actual attenuated response to these events, but is rather driven by larger P300 amplitudes following favourable outcomes (Yeung and Sanfey, 2004). Furthermore, the relative contribution of negative and positive outcomes to the FRN remains unclear due to the fact that many studies have employed the computation of a difference waveform to measure FRN magnitude (e.g., Dunning and Hajcak, 2007;Foti and Hajcak, 2009;Hajcak et al, 2007;Holroyd et al, 2008;Miltner et al, 1997), and other recent research has suggested that, rather than a negative deflection to non-reward outcomes, the FRN is better conceptualised as a positive deflection that is greater following reward compared to non-reward outcomes (Foti et al, 2011;Holroyd et al, 2003;Holroyd et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations